1994
DOI: 10.1038/368558a0
|View full text |Cite
|
Sign up to set email alerts
|

B61 is a ligand for the ECK receptor protein-tyrosine kinase

Abstract: A protein ligand for the ECK receptor protein-tyrosine kinase has been isolated by using the extracellular domain (ECK-X) of the receptor as an affinity reagent. Initially, concentrated cell culture supernatants were screened for receptor binding activity using immobilized ECK-X in a surface plasmon resonance detection system. Subsequently, supernatants from selected cell lines were fractionated directly by receptor affinity chromatography, resulting in the single-step purification of B61, a protein previously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
139
0
1

Year Published

1996
1996
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(145 citation statements)
references
References 15 publications
5
139
0
1
Order By: Relevance
“…This attachment is either mediated by a transmembrane domain (Lerk2, Beckmann et al, 1994;ELF-2, Bergemann et al, 1995) or through a linkage to a GPI tail (B61, Bartley et al, 1994;Ehk1-L, Davis et al, 1994;Lerk4, Kozlosky et al, 1995;AL-1, Winslow et al, 1995;and Elf-1, Cheng and Flanagan, 1994). To test whether the detected MDK1 ligand in mouse embryos is attached to the cell surface via a GPI linkage, whole mouse embryos were treated with phosphatidylinositol-speci®c phospholipase C (PI ± PLC), incubated with MDK1-AP and stained for bound AP activity (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This attachment is either mediated by a transmembrane domain (Lerk2, Beckmann et al, 1994;ELF-2, Bergemann et al, 1995) or through a linkage to a GPI tail (B61, Bartley et al, 1994;Ehk1-L, Davis et al, 1994;Lerk4, Kozlosky et al, 1995;AL-1, Winslow et al, 1995;and Elf-1, Cheng and Flanagan, 1994). To test whether the detected MDK1 ligand in mouse embryos is attached to the cell surface via a GPI linkage, whole mouse embryos were treated with phosphatidylinositol-speci®c phospholipase C (PI ± PLC), incubated with MDK1-AP and stained for bound AP activity (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…These studies together with the identi®cation of a number of ligands suggested a participation of eck/ eph related RTKs in a number of morphogenetic processes . For example, eck and its ligand B61 (Bartley et al, 1994), are involved in neuronal survival of rat spinal cord cultures (Magal et al, 1996) as well as in TNF-a induced angiogenesis . The identi®cation of RAGS as a repulsive axon guidance signal (Drescher et al, 1995) as well as the identi®cation of complementary gradients in receptor and ligand expression of Elf-1 and Mek-4 during the development of the topographic retinotectal projection map has led to the implication of the eck/eph subfamily of RTKs in axonal guidance.…”
Section: Introductionmentioning
confidence: 99%
“…The binding of ligands to their cognate Eph receptors on apposing cell surfaces results in autophosphorylation of the Eph receptor on tyrosines in the intracellular domain (Bartley et al, 1994;Davis et al, 1994). This has also been demonstrated for EphB2 (formerly designated Cek5, Nuk, or Sek-3) (Eph Nomenclature Committee, 1997) upon binding of its ligand ephrin-B1 (formerly Cek5-L or LERK2) (Shao et al, 1994;Holash et al, 1997).…”
Section: Introductionmentioning
confidence: 88%
“…Blood samples were collected on Day 18 following vector inoculation from four mice per group by the retro-orbital bleed under anesthesia to monitor the development of vector immunity by enzyme-linked immunosorbent assay (ELISA). Mice were killed with an overdose of an anesthetic when the tumors reached a volume of approximately 1000 mm 3 or on Day 48 postinoculation.…”
Section: Cell Viability Assaymentioning
confidence: 99%
“…1,2 In healthy breast epithelial cells, EphA2 is associated with one of its Ephrin ligands (A1-A5), predominantly 23 kDa EphrinA1. This binding leads to autophosphorylation of three tyrosine residues present in the intracytoplasmic domain of EphA2 [3][4][5][6] and then activates or inhibits other kinases before getting internalized and degraded. [7][8][9] Functionally altered EphA2 in invasive human breast cancer cells fails to bind to its ligand EphrinA1 leading to the accumulation of unphosphorylated EphA2.…”
mentioning
confidence: 99%